Pengaruh Sistem Keselamatan Dan Kesehatan Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Rumah Sakit Muhammadiyah Jombang - Ninik Ainur Rosyidah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This study aims to determine the Effect of Occupational Safety and Health Systems and the Physical Work Environment on the Performance of Employees of the Muhammadiyah Hospital in Jombang. The method used in this research is quantitative research method and uses an associative approach the result showed that : (1) Occupational Safety and Health have partial effect on the Performance of Employees of Jombang Muhammadiyah Hospital, (2) The Physical Work Environment has partial effect on Performance of Employees of the Muhammadiyah Jombang Hospital, (3) Occupational Safety Health Physical Work Environment simultaneously influence the Performance of Employees of the Jombang Muhammadiyah Hospital. Keywords: Occupational Health Safety; Physical Work Environment; Employee Performance